Cognition in the days following concussion: comparison of symptomatic versus asymptomatic athletes. Issue 2 (17th January 2006) - Collie, A; Makdissi, M; Maruff, P; Bennell, K; McCrory, P
Abstract : Background: Concussion is a common neurological injury occurring during contact sport. Current guidelines recommend that no athlete should return to play while symptomatic or displaying cognitive dysfunction. This study compared post-concussion cognitive function in recently concussed athletes who were symptomatic/asymptomatic at the time of assessment with that of non-injured (control) athletes. Methods: Prospective study of 615 male Australian Rules footballers. Before the season, all participants (while healthy) completed a battery of baseline computerised (CogSport) and paper and pencil cognitive tasks. Sixty one injured athletes (symptomatic = 25 and asymptomatic = 36) were reassessed within 11 days of being concussed; 84 controls were also reassessed. The serial cognitive function of the three groups was compared using analysis of variance. Results: The performance of the symptomatic group declined at the post-concussion assessment on computerised tests of simple, choice, and complex reaction times compared with the asymptomatic and control groups. The magnitude of changes was large according to conventional statistical criteria. On paper and pencil tests, the symptomatic group displayed no change at reassessment, whereas large improvements were seen in the other two groups. Conclusion: Injured athletes experiencing symptoms of concussion displayed impaired motor function and attention, although their learning and memory were preserved. These athletes displayed no change in performance on paper and pencil tests in contrast with the improvement observed in asymptomatic and non-injured athletes. Athletes experiencing symptoms of concussion should be withheld from training and competition until both symptoms and cognitive dysfunction have resolved.